FILSAFAT PENDIDIKAN DI INDONESIA: LANDASAN DALAM PEMBENTUKAN KARAKTER BANGSA DI ERA TANTANGAN GLOBALISASI - Mahbubi, M (Al Hikmah: Jurnal Tarbiyah dan Ilmu Keguruan, 2025)
This article explores the role of philosophy of education in Indonesia as a foundation for national character building, particularly amidst the challenges of globalization and technological advancement. It examines how Indonesian educational philosophy, influenced by Pancasila and local cultural values, fosters character development in students. The research positions education as a tool for shaping morally and ethically responsible individuals who can navigate the complexities of modernity while preserving national identity. The article discusses the integration of character education within the national curriculum and its relevance to contemporary societal needs. Key findings suggest that education grounded in philosophical principles can enhance resilience to global influences, ensuring the preservation of Indonesia’s cultural and moral values in the face of rapid technological changes and cultural globalization.